Virulence and antibiotic resistance of Klebsiella pneumoniae strains isolated from wastewater. (20th October 2021) - Cornacchia, A; Centorotola, G; Saletti, MA; Ciarrocchi, A; Marfoglia, C; Manzulli, V; Galante, D; Rodrigues, C; Brisse, S; Pomilio, F
Abstract: Background: Multidrug-resistant Klebsiella pneumoniae (Kp) strains are considered a global public health threat. The aim of the present study was to assess the occurrence of resistant and virulent Kp in Italian environmental wastewater, in order to evaluate the contribution of wastewater as reservoir of virulent and multidrug-resistant bacteria. Methods: Forty samples of wastewater were collected in six sampling sessions from June to November 2018 in Central Italy and processed to detect Kp. All the presumptive Kp colonies isolated were identified by MALDI-TOF MS (Bruker Daltonics, Germany), then the genome sequences of all the confirmed Kp were obtained using Illumina Sequencing. Finally, characterization of virulence and resistance genes was performed in silico using the BIGSdb-Kp database provided by the Institut Pasteur (http://bigsdb.web.pasteur.fr ). Results: Kp was detected in 32 out of 40 samples (80%) and all strains were confirmed as Kp by MALDI-TOF MS. Genotyping analysis showed that besides the native bla-SHV, bla-LEN, bla-OKP genes linked to β-lactams resistance, gyr and par genes, involved in quinolone resistance, and no other resistance genes were detected. Regarding virulence, all strains carried the fimbriae encoding gene mrk, associated with adhesion and biofilm formation. The ferric aerobactin receptor iutA was harbored by 3 strains (9.4%). The siderophore Yersiniabactin locus (ybtS, ybtX, ybtQ, ybtP, ybtA, irp2 irp1, ybtU, ybtT, ybtE, fyuA), essential for iron scavenging, is carried by 7 out of 32 strains (21.9%). Conclusions: Our results showed a high prevalence of Kp in wastewater that also harbored several resistance and virulence genes. These results make interesting to investigate more about wastewater as hot spots of enrichment, recombination, genetic exchange and selection of antibiotic resistant "super-bugs" that persisting and surviving in the environment could be a health risk for humans and animals. Key messages: Wastewater could play a role as Klebsiella pneumoniae reservoir of virulence and resistance genes that can disseminate into wildlife and reach humans. It's necessary a "one health" approach to deeply investigate about the presence of superbugs bacteria in the environment and the possible risks for human health.